2016
DOI: 10.3390/photonics3020028
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and Applications of External Cavity-QCLs towards Hyperspectral Imaging for Standoff Detection and Real-Time Spectroscopic Sensing of Chemicals

Abstract: External-cavity quantum cascade lasers (EC-QCL) are now established as versatile wavelength-tunable light sources for analytical spectroscopy in the mid-infrared (MIR) spectral range. We report on the realization of rapid broadband spectral tuning with kHz scan rates by combining a QCL chip with a broad gain spectrum and a resonantly driven micro-opto-electro-mechanical (MOEMS) scanner with an integrated diffraction grating in Littrow configuration. The capability for real-time spectroscopic sensing based on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(25 citation statements)
references
References 27 publications
0
24
0
1
Order By: Relevance
“…In pulsed operation, the typical spectral width 20 of its emission lies between 1 and 2 cm −1 . Changing to a cw-capable laser [chip #3, see Fig.…”
Section: Linewidth and Spectral Reproducibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…In pulsed operation, the typical spectral width 20 of its emission lies between 1 and 2 cm −1 . Changing to a cw-capable laser [chip #3, see Fig.…”
Section: Linewidth and Spectral Reproducibilitymentioning
confidence: 99%
“…With a tripod-mounted system with a large-aperture collection optics, small amounts of explosives and related precursors could be detected over distances of about 20 m with spectral scanning times on the order of 10 to 30 s. 20 Here, we present our first results obtained with a QCL-based handheld scanner designed to detect a wide range of substances on arbitrary surfaces over shorter distances of about 0.5 to 2 m. These developments are driven by the need of first responders for portable and simple-to-use detection hardware for fast identification of suspicious, potentially hazardous substances. Importantly, the technique works at eye-safe power levels.…”
Section: Backscattering Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…However, as the hyperspectral image bands are sequentially generated, a relative motion of the sensor and scene could potentially induce non-linear spectral mixing of adjacent materials in the resulting data set. In [10] a fast scanning single-element detector variant of the same principle is proposed that measures single spectra at a timescale of 1 ms and the required spatial information is obtained sequentially. It is shown that the measurement speed is sufficient for acquisition of hyperspectral observations in dynamic scenes (i.e.…”
Section: Evaluation Datamentioning
confidence: 99%
“…The development of quantum cascade lasers (QCL) and interband cascade lasers (ICLs) provides laser emission in the MIR and opened the important chemical fingerprint region to this technique [4][5][6][7][8]. In addition, external cavity quantum cascade laser (EC-QCL)-based spectroscopy proved to be suitable for highly resolved and wide-range spectroscopic sensing of a multitude of gases [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%